Early-Life Cognitive Activity Is Related to Reduced Neurodegeneration in Alzheimer Signature Regions in Late Life - Ko, Kang; Byun, Min Soo; Yi, Dahyun; Lee, Jun Ho; Kim, Chan Hyung; Lee, Dong Young (Frontiers in Aging Neuroscience, 2018)
Background: Although increased cognitive activity (CA), both current and past, is known to be associated with a decreased occurrence of Alzheimer’s disease (AD) dementia in older adults, the exact neural mechanisms underlying the association between CA during different stages of life and human dementia remain unclear. Therefore, we investigated whether CA during different life stages is associated with cerebral amyloid-beta (Aß) pathology and AD-related neurodegeneration in non-demented older adults. Methods: Cross-sectional analyses of data collected between April 2014 and March 2016 from the Korean Brain Aging Study for Early Diagnosis and Prediction of Alzheimer’s Disease (KBASE), an ongoing prospective cohort. In total, 321 community-dwelling, non-demented older adults were involved in this study. Cerebral Aß deposition and Aß positivity were measured using 11C-Pittsburgh compound B (PiB)-positron emission tomography (PET). AD-signature region cerebral glucose metabolism (AD-CMglu) and AD-related neurodegeneration (AD-ND) positivity were measured using 18F-fluorodeoxyglucose (FDG)-PET. In addition, CA in early, mid, and late life was systematically evaluated using a structured questionnaire. Results: Of the 321 participants, 254 were cognitively normal (CN) and 67 had mild cognitive impairment. The mean age of participants was 69.6 years old [standard deviation (SD) = 8.0]. Higher early-life CA was associated with significantly increased AD-CMglu (B = 0.035, SE = 0.013, P = .009) and a decreasing AD-ND trend (OR = 0.65, 95% CI 0.43–0.98, P = .04) but was not associated with Aß deposition or positivity. We observed no association between midlife CA and any AD-related brain changes. Late-life CA showed an association with both global Aß deposition and AD-CMglu, although it was not statistically significant. Sensitivity analyses controlling for current depression or conducted only for CN individuals revealed similar results. Conclusions: Our results suggest that CA in early life may be protective against late-life AD-related neurodegeneration, independently of cerebral Aß pathology. Keywords: Cognitive activity, early life, midlife, late life, Alzheimer’s disease, neurodegeneration, glucose metabolism, amyloid beta deposition, the KBASE study